Degradation of 2,4-D in sugarcane and African clover soils, and bromacil and dimethoate in citrus soils : microbiological and chemical studies - Sandmann, Eduard Rudolf Ignatius Clemens (Stellenbosch : Stellenbosch University, 2012)
Summary in English.